High-performance ordinary asphalt mixture and preparation method thereof
By using high-performance ordinary asphalt mixtures prepared with a specific proportion of raw materials such as basalt and carbide steel slag powder, the shortcomings of existing asphalt pavement materials in high temperature, low temperature, water stability and anti-reflection crack performance are solved, and higher pavement performance and lower maintenance costs are achieved.
Patent Information
- Application Number
- CN202510053901.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-15
AI Technical Summary
The existing asphalt pavement materials have shortcomings in high temperature stability, low temperature crack resistance, water stability and anti-reflection crack performance, resulting in low pavement performance and high maintenance costs.
A high-performance ordinary asphalt mixture consisting of basalt coarse aggregate, basalt fine aggregate, asphalt cement and filler mixed with carbide steel slag powder is used to improve the performance of the mixture by controlling the raw material ratio and process conditions.
It significantly improves the high-temperature stability, low-temperature crack resistance, water stability and anti-reflective crack performance of asphalt mixture, reduces material costs and construction difficulty, and reduces environmental pollution.
Smart Images

Figure CN119822689A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering materials, in particular to a high-performance common asphalt mixture and a preparation method thereof. Background Art
[0002] Asphalt pavement has become the preferred pavement material in my country's road construction due to its driving comfort, excellent performance, convenient construction, and ability to adapt to different traffic volumes and environmental conditions. However, with the increase of time and traffic volume, asphalt pavement will develop various diseases, such as cracks, rutting, loose peeling, surface oiling, potholes, subsidence, etc. These diseases not only affect the appearance of the road and driving comfort, but may also cause serious safety problems.
[0003] In order to ensure the performance of the road and improve the service life of the road surface, the current scientific researchers mainly take a series of measures from the aspects of optimal design of mix ratio, high-quality construction technology, selection of appropriate materials, regular maintenance and inspection, and the use of advanced detection technology and equipment to monitor changes in road conditions. Although the optimal design of mix ratio and high-quality construction technology can theoretically ensure the service life of asphalt pavement, due to various uncertain factors in the actual production process, there is a certain gap between the actual pavement paving situation and the design situation. At the same time, this requires high quality of machinery and equipment and personnel. Regular maintenance inspections and the use of advanced detection technology and equipment to monitor changes in road conditions are usually technical methods in the maintenance stage. For the pavement part where the initial disease is found, timely repair measures are taken to extend the service life of the pavement. This method requires a large number of personnel configuration and equipment monitoring, which will consume a lot of manpower, material resources and financial resources. Although the repaired pavement can barely support driving, it affects the driving comfort for the driver and affects the beauty of the entire road.
[0004] The selection of appropriate materials is the main research direction of scientific researchers, because the basic performance of asphalt pavement can be guaranteed by controlling the quality of raw materials. The disease of asphalt pavement is ultimately a specific manifestation of low pavement performance, which is mainly attributed to the lack of high temperature stability, low temperature crack resistance, water stability and anti-reflective cracking performance. Asphalt mixture is mainly composed of asphalt binder, coarse and fine aggregates, fillers, etc. At present, scientific researchers mainly improve the pavement performance of the mixture by using modified asphalt, special mixture pavement structure, selecting hard and wear-resistant aggregates, controlling the edges and corners of aggregates, adding various fibers, and adding special interlayer structures. However, there are also the following problems: how to balance the cost and compatibility of modified asphalt, how to ensure the technical complexity and construction difficulty of special mixtures, the limitation of aggregate resources and quality fluctuations, the long-term effectiveness of fiber-reinforced materials, and the functional durability of special interlayer structures. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a high-performance ordinary asphalt mixture and a preparation method thereof, which can improve the high-temperature stability, low-temperature crack resistance, water stability and anti-reflective crack performance of the asphalt mixture, ensure the road performance of the asphalt mixture, have the characteristics of low economic cost, simple construction process, low-carbon and environmentally friendly materials, and good road performance, and can be used for paving new asphalt pavements, quickly repairing old asphalt pavements, etc.
[0006] The technical solution adopted by the present invention to solve its technical problems is: a high-performance ordinary asphalt mixture, which is composed of the following raw materials in percentage by weight: 50% to 76% of basalt coarse aggregate, 19% to 40% of basalt fine aggregate, 4% to 6% of asphalt binder oilstone ratio, and 5% to 10% of filler mixed with carbonized steel slag powder; wherein the filler mixed with carbonized steel slag powder is composed of carbonized steel slag powder and ordinary limestone mineral powder, and the weight of the carbonized steel slag powder accounts for 20% to 100% of the total weight of the filler.
[0007] Furthermore, the present invention is composed of the following raw materials in weight percentage: 63% of the basalt coarse aggregate, 31% of the basalt fine aggregate, 4.8% of the asphalt binder oil-stone ratio, and 6% of the filler mixed with carbonized steel slag powder.
[0008] Furthermore, the weight of the carbonized steel slag powder of the present invention accounts for 90% of the total weight of the filler.
[0009] Furthermore, the particle sizes of the basalt coarse aggregate described in the present invention are 2.36mm, 4.75mm, 9.35mm and 13.2mm, and the particle sizes of the basalt fine aggregate are 0.075mm, 0.15mm, 0.3mm, 0.6mm and 1.18mm.
[0010] Furthermore, the particle size of the carbonized steel slag powder of the present invention is less than 45 μm, and the active CaO content in the carbonized steel slag powder should be less than 30%.
[0011] At the same time, the present invention also provides a method for preparing a high-performance common asphalt mixture, comprising the following steps:
[0012] Step 1: Put the coarse steel slag particles in a ball mill, grind the coarse particles into powder particles by controlling the grinding speed and grinding time, and then put the ground steel slag powder into a carbonization box for carbonization to obtain dry carbonized steel slag powder.
[0013] Step 2: Weigh the carburized steel slag powder and the ordinary limestone powder according to the specific gravity percentage, mix the weighed carburized steel slag powder and the ordinary limestone powder and stir them evenly for 3-8 minutes to obtain a filler mixed with carburized steel slag powder.
[0014] Step 3: Crush and screen the basalt, select clean aggregates with rough surface, needle-like particles content not more than 15%, and particle size of 2.36mm-13.2mm as basalt coarse aggregate, and select undifferentiated, impurity-free aggregates with a firmness of not less than 12% and a particle size of 0.075mm-1.18mm as basalt fine aggregate.
[0015] Step 4: At a mixing temperature of 155°C-165°C, mix the basalt coarse and fine aggregates in step 3, the filler mixed with carbonized steel slag powder in step 2, and the 70# matrix asphalt that has been preheated to a molten state according to the weight percentage of the raw materials until the asphalt in the mixture has fully coated the mineral particles, thereby obtaining a high-performance ordinary asphalt mixture.
[0016] Furthermore, the grinding time in step 1 of the present invention is 30 min, the grinding speed is 600 r / min, and the ball mill is an omnidirectional planetary F-P20E.
[0017] Furthermore, the carbonization equipment described in step 1 of the present invention is a HC-HTX12 carbonization test box, and the carbonization conditions are a temperature of 30° C., a relative humidity of 75%, a carbon dioxide concentration of about 28%, and a carbonization time of not less than 2 days.
[0018] Furthermore, the carbonization effect of the carbonized steel slag powder in step 1 of the present invention is determined by comprehensive testing of phenolphthalein titration and EDTA titration.
[0019] Furthermore, the mixing temperature of the mixture in step 4 of the present invention is 160° C., the mixing equipment of the mixture is a STLJ-5 asphalt mixture mixer, and the mixing time is 180 seconds.
[0020] The beneficial effects of the present invention are:
[0021] 1. The present invention uses industrial solid waste steel slag as filler, which can effectively reduce the space occupied by materials in landfills and reduce the consumption of land resources. By recycling steel slag, the pollution risk caused by it to soil, water and air is reduced, and the development of green transportation is promoted.
[0022] 2. The steel slag used in the present invention has lower cost than traditional mineral powder, especially when it is sourced locally, it can save transportation costs, and it reduces the demand for natural resources, which also helps to stabilize the price of raw materials.
[0023] 3. The mineral composition of the carburized steel slag powder used in the present invention is relatively stable. The carburized steel slag powder is mainly composed of metal oxides such as calcium and iron. After high-temperature treatment, a hard crystal structure is formed, which gives it higher hardness and wear resistance, which helps to improve the compressive strength and wear resistance of asphalt mixture.
[0024] 4. The present invention adopts asphalt mixture in which solid waste filler partially or completely replaces mineral powder filler. Compared with limestone mineral powder, it can increase the internal friction of the asphalt mixture, thereby effectively resisting deformation caused by vehicle load, reducing the occurrence of rutting, and improving the high-temperature stability of the mixture. Moreover, it can form a better bonding effect with asphalt. Carbonized steel slag powder has a lower water absorption rate and better density, which can reduce the possibility of water intrusion and improve the water stability of the asphalt mixture.
[0025] 5. Compared with the mining and processing of natural ores, the energy consumption required to produce fillers using steel slag is less, which indirectly reduces greenhouse gas emissions. Moreover, steel slag has a strong carbon adsorption capacity and can effectively reduce carbon dioxide in high-carbon emission industrial production, which meets the requirements of energy conservation, emission reduction and green development. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the microscopic particle size diagram of carburized steel slag powder;
[0027] Figure 2 The particle size distribution of carbonized steel slag powder;
[0028] Figure 3 is the dynamic stability value of the mixture;
[0029] Figure 4 is the failure bending-tensile strain of the mixture;
[0030] Figure 5 This is the result of the water immersion Marshall test;
[0031] Figure 6 This is the freeze-thaw splitting test result diagram;
[0032] Figure 7 The maximum load and load loss rate of the mixture at 25°C;
[0033] Figure 8 This is the frequency scan diagram of asphalt mortar. DETAILED DESCRIPTION
[0034] The present invention will now be described in further detail in conjunction with the accompanying drawings and preferred embodiments. These drawings are simplified schematic diagrams, which only illustrate the basic structure of the present invention in a schematic manner, and therefore only show the components related to the present invention.
[0035] Example 1
[0036] The high-performance ordinary asphalt mixture of this embodiment is composed of the following raw materials in weight percentage: 52% basalt coarse aggregate, 42% basalt fine aggregate, 4.8% asphalt binder oil-stone ratio, and 6% filler mixed with carburized steel slag powder; the filler mixed with carburized steel slag powder is composed of carburized steel slag powder and ordinary limestone mineral powder, and the weight of the carburized steel slag powder accounts for 25% of the total weight of the filler.
[0037] In this embodiment, the basalt coarse aggregate, basalt fine aggregate and filler are collectively referred to as aggregate. The particle sizes of the basalt coarse aggregate are 2.36 mm, 4.75 mm, 9.5 mm and 13.2 mm, the basalt coarse aggregate with a particle size of 2.36 mm accounts for 12% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 4.75 mm accounts for 16% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 9.5 mm accounts for 10% of the total mass of the aggregate, and the basalt coarse aggregate with a particle size of 13.2 mm accounts for 11% of the total mass of the aggregate.
[0038] The particle sizes of the basalt fine aggregate are 0.075mm, 0.15mm, 0.3mm, 0.6mm and 1.18mm, the basalt coarse aggregate with a particle size of 0.075mm accounts for 5% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.15mm accounts for 4% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.3mm accounts for 12% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.6mm accounts for 10% of the total mass of the aggregate, and the basalt coarse aggregate with a particle size of 1.18mm accounts for 11% of the total mass of the aggregate.
[0039] In this embodiment, the particle size of the carbonized steel slag powder is less than 45 μm, and the active CaO content in the carbonized steel slag powder should be less than 30%.
[0040] The method for preparing the high-performance common asphalt mixture of this embodiment comprises the following steps:
[0041] Step 1: Put the coarse steel slag particles in a full-range planetary F-P20E ball mill, set the grinding speed to 500r / min and the grinding time to 25min, grind the coarse particles into powder particles, and then put the ground steel slag powder into the HC-HTX12 carbonization test box for carbonization, the carbonization temperature is 32°C, the relative humidity is 77%, the carbon dioxide concentration is 18%, and the carbonization time is 3d. To obtain dry carbonized steel slag powder.
[0042] Step 2: weigh the carburized steel slag powder and the ordinary limestone ore powder according to the specific gravity percentage, mix the weighed carburized steel slag powder and the ordinary limestone ore powder and stir them evenly for 6 minutes to obtain a filler mixed with carburized steel slag powder.
[0043] Step 3: Crush and screen the basalt, select clean aggregates with rough surface, needle-like particles content not more than 15%, and particle size of 2.36mm-13.2mm as basalt coarse aggregate, and select undifferentiated, impurity-free aggregates with a firmness of not less than 12% and a particle size of 0.075mm-1.18mm as basalt fine aggregate.
[0044] Step 4: Place the filler mixed with carbonized steel slag powder obtained in step 2 in an oven at 160°C for heat preservation and set aside, place the basalt coarse and fine aggregate obtained in step 3 in an oven at 165°C for heat preservation and set aside, and place the 70# matrix asphalt in an oven at 155°C for heat preservation and set aside.
[0045] Step 5: At a mixing pot preheated to 165°C, first pour the basalt coarse and fine aggregates in step 3 and the 70# matrix asphalt preheated to a molten state into the STLJ-5 asphalt mixture mixer according to the specified mass and stir for 1 minute. Then pour the filler mixed with carbonized steel slag powder in step 2 into the mixing pot and stir for 3 minutes to ensure that the asphalt in the mixture has fully coated the mineral particles. Finally, when the temperature of the mixture drops to room temperature, a high-performance ordinary asphalt mixture is obtained.
[0046] The asphalt mixture sample prepared in this embodiment needs to be softened and formed at 160°C. The Marshall specimen specifications for water stability performance adopt a cylindrical specimen with a diameter of 101.6mm and a height of 63.5mm. The rutting plate for high temperature stability adopts a rectangular specimen of 300mm×300mm×50mm. The small beam specimen for low temperature stability is a prismatic specimen of 250mm×30mm×35mm. The OT test uses a 150mm×75mm×38mm rectangular standard specimen.
[0047] Example 2
[0048] The high-performance ordinary asphalt mixture of this embodiment is composed of the following raw materials in weight percentage: 7% basalt coarse aggregate, 43% basalt fine aggregate, 5.4% asphalt binder oil-stone ratio, and 50% filler mixed with carburized steel slag powder; the filler mixed with carburized steel slag powder is composed of carburized steel slag powder and ordinary limestone mineral powder, and the weight of the carburized steel slag powder accounts for 42% of the total weight of the filler.
[0049] In this embodiment, the basalt coarse aggregate, basalt fine aggregate and filler are collectively referred to as aggregate. The particle sizes of the basalt coarse aggregate are 2.36 mm, 4.75 mm, 9.5 mm and 13.2 mm, the basalt coarse aggregate with a particle size of 2.36 mm accounts for 12% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 4.75 mm accounts for 20% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 9.5 mm accounts for 16% of the total mass of the aggregate, and the basalt coarse aggregate with a particle size of 13.2 mm accounts for 2% of the total mass of the aggregate.
[0050] The particle sizes of the basalt fine aggregate are 0.075mm, 0.15mm, 0.3mm, 0.6mm and 1.18mm, the basalt coarse aggregate with a particle size of 0.075mm accounts for 3% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.15mm accounts for 5% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.3mm accounts for 9% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.6mm accounts for 8% of the total mass of the aggregate, and the basalt coarse aggregate with a particle size of 1.18mm accounts for 18% of the total mass of the aggregate.
[0051] In this embodiment, the particle size of the carbonized steel slag powder is μm, and the active CaO content in the carbonized steel slag powder should be less than 30%.
[0052] The method for preparing the high-performance common asphalt mixture of this embodiment comprises the following steps:
[0053] Step 1: Put the coarse steel slag particles in a full-range planetary F-P20E ball mill, set the grinding speed to 450r / min and the grinding time to 30min, grind the coarse particles into powder particles, and then put the ground steel slag powder into the HC-HTX12 carbonization test box for carbonization, the carbonization temperature is 28°C, the relative humidity is 75%, the carbon dioxide concentration is 22%, and the carbonization time is 2d. To obtain dry carbonized steel slag powder.
[0054] Step 2: weigh the carburized steel slag powder and the ordinary limestone ore powder according to the specific gravity percentage, mix the weighed carburized steel slag powder and the ordinary limestone ore powder and stir them evenly for 5 minutes to obtain a filler mixed with carburized steel slag powder.
[0055] Step 3: Crush and screen the basalt, select clean aggregates with rough surface, needle-like particles content not more than 15%, and particle size of 2.36mm-13.2mm as basalt coarse aggregate, and select undifferentiated, impurity-free aggregates with a firmness of not less than 12% and a particle size of 0.075mm-1.18mm as basalt fine aggregate.
[0056] Step 4: Place the filler mixed with carbonized steel slag powder obtained in step 2 in an oven at 165°C for heat preservation and set aside, place the basalt coarse and fine aggregate obtained in step 3 in an oven at 165°C for heat preservation and set aside, and place 70# matrix asphalt in an oven at 160°C for heat preservation and set aside.
[0057] Step 5: At a mixing pot preheated to 165°C, first pour the basalt coarse and fine aggregates in step 3 and the 70# matrix asphalt preheated to a molten state into the STLJ-5 asphalt mixture mixer according to the specified mass and stir for 1 minute. Then pour the filler mixed with carbonized steel slag powder in step 2 into the mixing pot and stir for 3 minutes to ensure that the asphalt in the mixture has fully coated the mineral particles. Finally, when the temperature of the mixture drops to room temperature, a high-performance ordinary asphalt mixture is obtained.
[0058] The asphalt mixture sample prepared in this embodiment needs to be softened and formed at 160°C. The Marshall specimen specifications for water stability performance adopt a cylindrical specimen with a diameter of 101.6mm and a height of 63.5mm. The rutting plate for high temperature stability adopts a rectangular specimen of 300mm×300mm×50mm. The small beam specimen for low temperature stability is a prismatic specimen of 250mm×30mm×35mm. The OT test uses a 150mm×75mm×38mm rectangular standard specimen.
[0059] Example 3
[0060] The high-performance ordinary asphalt mixture of this embodiment is composed of the following raw materials in weight percentage: 58% basalt coarse aggregate, 37% basalt fine aggregate, 5.2% asphalt binder oil-stone ratio, and 5% filler mixed with carburized steel slag powder; the filler mixed with carburized steel slag powder is composed of carburized steel slag powder and ordinary limestone mineral powder, and the weight of the carburized steel slag powder accounts for 65% of the total weight of the filler.
[0061] In this embodiment, the basalt coarse aggregate, basalt fine aggregate and filler are collectively referred to as aggregate. The particle sizes of the basalt coarse aggregate are 2.36 mm, 4.75 mm, 9.5 mm and 13.2 mm, the basalt coarse aggregate with a particle size of 2.36 mm accounts for 22% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 4.75 mm accounts for 16% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 9.5 mm accounts for 18% of the total mass of the aggregate, and the basalt coarse aggregate with a particle size of 13.2 mm accounts for 2% of the total mass of the aggregate.
[0062] The particle sizes of the basalt fine aggregate are 0.075mm, 0.15mm, 0.3mm, 0.6mm and 1.18mm, the basalt coarse aggregate with a particle size of 0.075mm accounts for 5% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.15mm accounts for 7% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.3mm accounts for 9% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.6mm accounts for 8% of the total mass of the aggregate, and the basalt coarse aggregate with a particle size of 1.18mm accounts for 8% of the total mass of the aggregate.
[0063] In this embodiment, the particle size of the carbonized steel slag powder is less than 45 μm, and the active CaO content in the carbonized steel slag powder should be less than 30%.
[0064] The method for preparing the high-performance common asphalt mixture of this embodiment comprises the following steps:
[0065] Step 1: Put the coarse steel slag particles in a full-range planetary F-P20E ball mill, set the grinding speed to 450r / min and the grinding time to 25min, grind the coarse particles into powder particles, and then put the ground steel slag powder into the HC-HTX12 carbonization test box for carbonization, the carbonization temperature is 27°C, the relative humidity is 76%, the carbon dioxide concentration is 22%, and the carbonization time is 3d. To obtain dry carbonized steel slag powder.
[0066] Step 2: weigh the carburized steel slag powder and the ordinary limestone ore powder according to the specific gravity percentage, mix the weighed carburized steel slag powder and the ordinary limestone ore powder and stir them evenly for 8 minutes to obtain a filler mixed with carburized steel slag powder.
[0067] Step 3: Crush and screen the basalt, select clean aggregates with rough surface, needle-like particles content not more than 15%, and particle size of 2.36mm-13.2mm as basalt coarse aggregate, and select undifferentiated, impurity-free aggregates with a firmness of not less than 12% and a particle size of 0.075mm-1.18mm as basalt fine aggregate.
[0068] Step 4: Place the filler mixed with carbonized steel slag powder obtained in step 2 in an oven at 155°C for heat preservation and standby use, place the basalt coarse and fine aggregate obtained in step 3 in an oven at 150°C for heat preservation and standby use, and place 70# matrix asphalt in an oven at 150°C for heat preservation and standby use.
[0069] Step 5: At a mixing pot preheated to 165°C, first pour the basalt coarse and fine aggregates in step 3 and the 70# matrix asphalt preheated to a molten state into the STLJ-5 asphalt mixture mixer according to the specified mass and stir for 1 minute. Then pour the filler mixed with carbonized steel slag powder in step 2 into the mixing pot and stir for 3 minutes to ensure that the asphalt in the mixture has fully coated the mineral particles. Finally, when the temperature of the mixture drops to room temperature, a high-performance ordinary asphalt mixture is obtained.
[0070] The asphalt mixture sample prepared in this embodiment needs to be softened and formed at 160°C. The Marshall specimen specifications for water stability performance adopt a cylindrical specimen with a diameter of 101.6mm and a height of 63.5mm. The rutting plate for high temperature stability adopts a rectangular specimen of 300mm×300mm×50mm. The small beam specimen for low temperature stability is a prismatic specimen of 250mm×30mm×35mm. The OT test uses a 150mm×75mm×38mm rectangular standard specimen.
[0071] Example 4
[0072] The high-performance ordinary asphalt mixture of this embodiment is composed of the following raw materials in weight percentage: 55% of basalt coarse aggregate, 38.5% of basalt fine aggregate, 4.6% of asphalt binder oil-stone ratio, and 6.5% of filler mixed with carbonized steel slag powder; wherein the filler mixed with carbonized steel slag powder is composed of carbonized steel slag powder and ordinary limestone mineral powder, and the weight of the carbonized steel slag powder accounts for 88% of the total weight of the filler.
[0073] In this embodiment, the basalt coarse aggregate, basalt fine aggregate and filler are collectively referred to as aggregate. The particle sizes of the basalt coarse aggregate are 2.36 mm, 4.75 mm, 9.5 mm and 13.2 mm, the basalt coarse aggregate with a particle size of 2.36 mm accounts for 18% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 4.75 mm accounts for 15% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 9.5 mm accounts for 19% of the total mass of the aggregate, and the basalt coarse aggregate with a particle size of 13.2 mm accounts for 3% of the total mass of the aggregate.
[0074] The particle sizes of the basalt fine aggregate are 0.075mm, 0.15mm, 0.3mm, 0.6mm and 1.18mm, the basalt coarse aggregate with a particle size of 0.075mm accounts for 5.5% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.15mm accounts for 6% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.3mm accounts for 9% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.6mm accounts for 9% of the total mass of the aggregate, and the basalt coarse aggregate with a particle size of 1.18mm accounts for 9% of the total mass of the aggregate.
[0075] In this embodiment, the particle size of the carbonized steel slag powder is less than 45 μm, and the active CaO content in the carbonized steel slag powder should be less than 30%.
[0076] The method for preparing the high-performance common asphalt mixture of this embodiment comprises the following steps:
[0077] Step 1: Put the coarse steel slag particles in a full-range planetary F-P20E ball mill, set the grinding speed to 400r / min and the grinding time to 40min, grind the coarse particles into powder particles, and then put the ground steel slag powder into the HC-HTX12 carbonization test box for carbonization, the carbonization temperature is 30℃, the relative humidity is 73%, the carbon dioxide concentration is 20%, and the carbonization time is 2d. To obtain dry carbonized steel slag powder.
[0078] Step 2: weigh the carburized steel slag powder and the ordinary limestone ore powder according to the specific gravity percentage, mix the weighed carburized steel slag powder and the ordinary limestone ore powder and stir them evenly for 6 minutes to obtain a filler mixed with carburized steel slag powder.
[0079] Step 3: Crush and screen the basalt, select clean aggregates with rough surface, needle-like particles content not more than 15%, and particle size of 2.36mm-13.2mm as basalt coarse aggregate, and select undifferentiated, impurity-free aggregates with a firmness of not less than 12% and a particle size of 0.075mm-1.18mm as basalt fine aggregate.
[0080] Step 4: Place the filler mixed with carbonized steel slag powder obtained in step 2 in an oven at 160°C for heat preservation and standby use, place the basalt coarse and fine aggregate obtained in step 3 in an oven at 155°C for heat preservation and standby use, and place the 70# matrix asphalt in an oven at 150°C for heat preservation and standby use.
[0081] Step 5: At a mixing pot preheated to 165°C, first pour the basalt coarse and fine aggregates in step 3 and the 70# matrix asphalt preheated to a molten state into the STLJ-5 asphalt mixture mixer according to the specified mass and stir for 1 minute. Then pour the filler mixed with carbonized steel slag powder in step 2 into the mixing pot and stir for 3 minutes to ensure that the asphalt in the mixture has fully coated the mineral particles. Finally, when the temperature of the mixture drops to room temperature, a high-performance ordinary asphalt mixture is obtained.
[0082] The asphalt mixture sample prepared in this embodiment needs to be softened and formed at 160°C. The Marshall specimen specifications for water stability performance adopt a cylindrical specimen with a diameter of 101.6mm and a height of 63.5mm. The rutting plate for high temperature stability adopts a rectangular specimen of 300mm×300mm×50mm. The small beam specimen for low temperature stability is a prismatic specimen of 250mm×30mm×35mm. The OT test uses a 150mm×75mm×38mm rectangular standard specimen.
[0083] Example 5
[0084] The high-performance ordinary asphalt mixture of this embodiment is composed of the following raw materials in weight percentage: 63% basalt coarse aggregate, 31% basalt fine aggregate, 5% asphalt binder oil-stone ratio, and 6% filler mixed with carburized steel slag powder; wherein the filler mixed with carburized steel slag powder is composed of carburized steel slag powder and ordinary limestone mineral powder, and the weight of the carburized steel slag powder accounts for 100% of the total weight of the filler.
[0085] In this embodiment, the basalt coarse aggregate, basalt fine aggregate and filler are collectively referred to as aggregate. The particle sizes of the basalt coarse aggregate are 2.36 mm, 4.75 mm, 9.5 mm and 13.2 mm, the basalt coarse aggregate with a particle size of 2.36 mm accounts for 16% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 4.75 mm accounts for 23.5% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 9.5 mm accounts for 18.5% of the total mass of the aggregate, and the basalt coarse aggregate with a particle size of 13.2 mm accounts for 5% of the total mass of the aggregate.
[0086] The particle sizes of the basalt fine aggregate are 0.075mm, 0.15mm, 0.3mm, 0.6mm and 1.18mm, the basalt coarse aggregate with a particle size of 0.075mm accounts for 4% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.15mm accounts for 3.5% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.3mm accounts for 5.5% of the total mass of the aggregate, the basalt coarse aggregate with a particle size of 0.6mm accounts for 7.5% of the total mass of the aggregate, and the basalt coarse aggregate with a particle size of 1.18mm accounts for 10.5% of the total mass of the aggregate.
[0087] In this embodiment, the particle size of the carbonized steel slag powder is less than 45 μm, and the active CaO content in the carbonized steel slag powder should be less than 30%.
[0088] The method for preparing the high-performance common asphalt mixture of this embodiment comprises the following steps:
[0089] Step 1: Put the coarse steel slag particles in a full-range planetary F-P20E ball mill, set the grinding speed to 500r / min and the grinding time to 30min, grind the coarse particles into powder particles, and then put the ground steel slag powder into the HC-HTX12 carbonization test box for carbonization, the carbonization temperature is 28°C, the relative humidity is 75%, the carbon dioxide concentration is 25%, and the carbonization time is 3d. To obtain dry carbonized steel slag powder.
[0090] Step 2: weigh the carburized steel slag powder and the ordinary limestone ore powder according to the specific gravity percentage, mix the weighed carburized steel slag powder and the ordinary limestone ore powder and stir them evenly for 5 minutes to obtain a filler mixed with carburized steel slag powder.
[0091] Step 3: Crush and screen the basalt, select clean aggregates with rough surface, needle-like particles content not more than 15%, and particle size of 2.36mm-13.2mm as basalt coarse aggregate, and select undifferentiated, impurity-free aggregates with a firmness of not less than 12% and a particle size of 0.075mm-1.18mm as basalt fine aggregate.
[0092] Step 4: Place the filler mixed with carbonized steel slag powder obtained in step 2 in an oven at 165°C for heat preservation and set aside, place the basalt coarse and fine aggregate obtained in step 3 in an oven at 160°C for heat preservation and set aside, and place the 70# matrix asphalt in an oven at 150°C for heat preservation and set aside.
[0093] Step 5: At a mixing pot preheated to 165°C, first pour the basalt coarse and fine aggregates in step 3 and the 70# matrix asphalt preheated to a molten state into the STLJ-5 asphalt mixture mixer according to the specified mass and stir for 1 minute. Then pour the filler mixed with carbonized steel slag powder in step 2 into the mixing pot and stir for 3 minutes to ensure that the asphalt in the mixture has fully coated the mineral particles. Finally, when the temperature of the mixture drops to room temperature, a high-performance ordinary asphalt mixture is obtained.
[0094] The asphalt mixture sample prepared in this embodiment needs to be softened and formed at 160°C. The Marshall specimen specifications for water stability performance adopt a cylindrical specimen with a diameter of 101.6mm and a height of 63.5mm. The rutting plate for high temperature stability adopts a rectangular specimen of 300mm×300mm×50mm. The small beam specimen for low temperature stability is a prismatic specimen of 250mm×30mm×35mm. The OT test uses a 150mm×75mm×38mm rectangular standard specimen.
[0095] The performance of the high-performance ordinary asphalt mixtures prepared in Examples 1 to 5 is experimentally analyzed below.
[0096] 1. High temperature stability
[0097] According to the relevant provisions of the test procedures, standard size rutting plates are formed. The rutting samples are placed in an environmental box at 60℃ for more than 5 hours to ensure constant temperature of the samples. After 1 hour of testing, the deformation and dynamic stability of the samples are obtained. Figure 1 This is the microscopic particle size diagram of carburized steel slag powder. Figure 2 The particle size distribution of carburized steel slag powder tested by particle size analyzer. Figure 3 The figure is a graph of dynamic stability values of different carbonized steel slag powder dosages in wheel rolling test, which is used to evaluate the high-temperature resistance of asphalt mixture to permanent deformation.
[0098] According to the test data, the addition of carbonized steel slag powder filler improves the dynamic stability value of asphalt mixture, which is far higher than the standard requirement of the mixture structure greater than or equal to 2400 times / mm. With the increase of carbonized steel slag powder content, the dynamic stability value is higher, especially in the 100% replacement asphalt mixture, its dynamic stability value is increased by 43.5%, which greatly improves the road surface's anti-rutting ability.
[0099] 2. Low temperature crack resistance
[0100] The bending test is used to evaluate the low-temperature effect of the pavement structure. The sample needs to be placed in an environmental chamber at -10°C for more than 60 minutes to keep the specimen temperature constant. The contact loading rate needs to be set to 50mm / min during the test, and the destructive flexural strain is used to determine the low-temperature performance of the mixture. Figure 4 The flexural strain diagram of asphalt mixture with different carbonized steel slag powder dosages.
[0101] from Figure 4 As shown in the low-temperature crack resistance performance diagram, the addition of carbonized steel slag powder increases the bending and tensile strain of the mixture beam. Since carbonized steel slag powder has a higher strength than mineral powder itself, the mixture can withstand greater strain under the same load, which improves the low-temperature crack resistance of the mixture. Compared with mineral powder, carbonized steel slag powder has better adhesion strength with asphalt, which helps the mixture resist cracking in low-temperature environments. In particular, the bending and tensile strain energy of the mixture sample with the largest demand for carbonized steel slag powder reaches 4154με.
[0102] 3. Water stability
[0103] The Marshall test includes the immersion Marshall test and the freeze-thaw splitting test to comprehensively evaluate the water stability of the pavement structure. The test samples are in accordance with the specifications. The immersion Marshall test uses two groups of tests, one group is kept in a 60℃ water bath for 40 minutes, and the other group is kept in a 60℃ water bath for 48 hours, and their Marshall stability values are tested respectively. The freeze-thaw splitting test is to place a group of 4 samples indoors, and another group of 4 samples are first saturated with 98±0.7kpa vacuum for 15 minutes and then stand still, then freeze in an environmental room at -18℃ for 16 hours, and then keep a constant temperature in a water bath at 60℃ for 24 hours, and finally all 8 samples are placed in a water bath at 25℃ for 2 hours to test their splitting strength and take the average value. Figure 5 The stability value, residual stability and specification requirements of asphalt mixture with different carbonized steel slag powder dosages. Figure 6 The splitting tensile strength of asphalt mixture with different carbonized steel slag powder dosage.
[0104] from Figure 5 It can be seen that the stability of carbonized steel slag powder-asphalt mixture in the 30-40min test and the stability of carbonized steel slag powder-asphalt mixture in the 48h test are both higher than that of mineral powder-asphalt mixture. From the bar chart of water-soaked residual stability, it can be seen that the residual stability of the control group is 85.9%, and the Marshall residual stability of 25% is 84.6%, which is lower than the control group, but also 4.6 percentage points higher than the limit value required by the specification. The water stability of the Marshall residual stability of 100% is excellent, and its residual stability value reaches 96.7%. This shows that the addition of carbonized steel slag powder can affect the water stability of asphalt mixture. Figure 6 In order to evaluate the water stability of the mixture by freeze-thaw splitting test, the addition of carbonized steel slag powder increased the splitting tensile strength of the asphalt mixture. The freeze-thaw splitting strength ratio obtained by the test shows that the asphalt mixture filled with carbonized steel slag powder can meet the 80% limit of the specification requirements, and its law is consistent with the results of the water stability evaluation by immersion test. This shows that the carbonized steel slag powder asphalt mixture has excellent anti-water damage effect.
[0105] 4. Anti-reflective crack performance
[0106] The Overlay Tester (OT) instrument was used for testing. The sample was formed using a rotary compactor to form a Ф15cm×5cm Marshall specimen, which was then cut into 15cm×7.5cm×3.8cm rectangular standard specimens according to the test requirements. The dried rectangular sample was placed on a base plate coated with epoxy resin and pressed with a pressure block for 12 hours. The specimen and the pressure plate were then placed in the instrument at 25°C for 4 hours. The test parameters set were: loading cycle of 10s, cyclic triangular displacement control mode, peak displacement of 0.625mm, and the test termination condition was when the load loss rate reached 93% or the test cycle reached 1200 times. The two major indicators, the maximum initial load of the first loading cycle and the peak load loss rate after 1200 loading cycles, were used to evaluate the anti-cracking performance of asphalt mixtures. The specific test data results can be seen in Figure 7 .
[0107] from Figure 7 It can be seen that the mixture with full carbonized steel slag powder has excellent anti-reflective cracking performance. Compared with ordinary asphalt mixture, it has excellent anti-cracking strength and lower crack extension rate. From the two judgment indicators of maximum load and load loss rate, it can be seen that the anti-reflective cracking effect of the mixture becomes better with the increase of carbonized steel slag content.
[0108] 5. Viscoelasticity of adhesive
[0109] Asphalt mixture is composed of asphalt, aggregate, etc. The performance test of asphalt material can indirectly reflect the mechanical properties of the mixture. The asphalt mortar formed by mixing carbonized steel slag powder with asphalt used in this paper can characterize the performance effect of steel slag powder in asphalt or mixture. The mechanical response of asphalt material changes with temperature and application frequency, and shows similar viscoelastic characteristics at higher temperature and lower frequency, and at lower temperature and higher frequency. Figure 8 It is the frequency sweep shear modulus of the sample of asphalt mortar measured by dynamic shear rheometer (DSR), and the specific test conditions are: temperature test condition of 60°C, frequency of 0.1rad / s-100rad / s, 100 frequency measurement points, and strain value of 0.5%.
[0110] Depend on Figure 8 It can be seen that the main curves of the complex shear modulus of asphalt mortar are all smooth and continuous, indicating that they are all simple rheological materials, and the compatibility of carbonized steel slag powder with asphalt is good. It can be seen from the figure that the high-frequency complex shear modulus is quite different. Considering that high frequency corresponds to low temperature, the larger the high-frequency complex shear modulus, the stronger the low-temperature crack resistance. Therefore, the addition of carbonized steel slag powder improves the low-temperature performance of the material, and the greater the content, the better the performance, which is consistent with the results of the beam bending test.
[0111] The above description only describes the specific implementation mode of the present invention. Various examples do not limit the essential content of the present invention. After reading the description, ordinary technicians in the relevant technical field can modify or deform the specific implementation modes described above without departing from the essence and scope of the invention.
Claims
1. A high-performance common asphalt mixture, characterized by: The invention comprises the following raw materials in weight percentage: 50% to 76% of basalt coarse aggregate, 19% to 40% of basalt fine aggregate, 4% to 6% of asphalt binder oil-stone ratio, and 5% to 10% of filler mixed with carburized steel slag powder; wherein the filler mixed with carburized steel slag powder consists of carburized steel slag powder and ordinary limestone ore powder, and the weight of the carburized steel slag powder accounts for 20% to 100% of the total weight of the filler.
2. A high performance common asphalt mixture as claimed in claim 1, characterized in that: The invention is composed of the following raw materials in the following weight percentages: 63% of the basalt coarse aggregate, 31% of the basalt fine aggregate, 4.8% of the asphalt binder oil-stone ratio, and 6% of the filler mixed with carbonized steel slag powder.
3. A high performance common asphalt mixture as claimed in claim 1, characterized in that: The weight of the carbonized steel slag powder accounts for 90% of the total weight of the filler.
4. A high performance common asphalt mixture as claimed in claim 1 or 2, characterized in that: The particle sizes of the basalt coarse aggregate are 2.36mm, 4.75mm, 9.35mm and 13.2mm, and the particle sizes of the basalt fine aggregate are 0.075mm, 0.15mm, 0.3mm, 0.6mm and 1.18mm.
5. A high performance common asphalt mixture as claimed in claim 1 or 3, characterized in that: The particle size of the carbonized steel slag powder is less than 45 μm, and the active CaO content in the carbonized steel slag powder should be less than 30%.
6. A method for preparing a high-performance common asphalt mixture as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Put the coarse steel slag particles in a ball mill, and grind the coarse particles into powder particles by controlling the grinding speed and grinding time. Then put the ground steel slag powder into a carbonization box for carbonization to obtain dry carbonized steel slag powder. Step 2: weigh the carburized steel slag powder and the ordinary limestone powder according to the specific gravity percentage, mix the weighed carburized steel slag powder and the ordinary limestone powder and stir them evenly for 3-8 minutes to obtain a filler mixed with carburized steel slag powder; Step 3: crush and screen the basalt, select clean aggregates with rough surface needle-like particles not more than 15% and a particle size of 2.36mm-13.2mm as basalt coarse aggregates, and select undifferentiated, impurity-free aggregates with a firmness of not less than 12% and a particle size of 0.075mm-1.18mm as basalt fine aggregates; Step 4: At a mixing temperature of 155°C-165°C, mix the basalt coarse and fine aggregates in step 3, the filler mixed with carbonized steel slag powder in step 2, and the 70# matrix asphalt that has been preheated to a molten state according to the weight percentage of the raw materials until the asphalt in the mixture has fully coated the mineral particles, thereby obtaining a high-performance ordinary asphalt mixture.
7. A high performance common asphalt mixture as claimed in claim 6, characterized in that: The grinding time in step 1 is 30 min, the grinding speed is 600 r / min, and the ball mill is an omnidirectional planetary F-P20E.
8. A high performance common asphalt mixture as claimed in claim 6, characterized in that: The carbonization equipment described in step 1 is a HC-HTX12 carbonization test box, the carbonization conditions are a temperature of 30° C., a relative humidity of 75%, a carbon dioxide concentration of about 28%, and a carbonization time of not less than 2 days.
9. A high performance common asphalt mixture as claimed in claim 6, characterized in that: The carbonization effect of the carbonized steel slag powder in the step 1 is determined by comprehensive testing of phenolphthalein titration and EDTA titration.
10. A high performance common asphalt mixture as claimed in claim 6, characterized in that: The mixing temperature of the mixture in step 4 is 160° C., the mixing equipment of the mixture is a STLJ-5 asphalt mixture mixer, and the mixing time is 180 seconds.